2002
DOI: 10.17221/4476-hortsci
|View full text |Cite
|
Sign up to set email alerts
|

Testing of wood hardiness to winter freezes in selections from progenies of Cerapadus × Prunus avium L. crosses

Abstract: Winter hardiness of genotypes pre-selected from Cerapadus × Prunus avium L. crosses was studied for 3 years (2000)(2001)(2002) in comparison with clonal cherry rootstocks, presently grown in the Czech Republic using artificial freezing of the budwood applied just after the phase of deep dormancy. With a temperature drop to freezing, both the mean and the maximum rate of general frost injury was markedly increased. The greatest damage of the tested material (roughly at the level of LD 50 on the average) occurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Cerapadus was produced in Russia by I. V. Michurin in 1935 from a cross of cherry 'Ideal' (Prunus fruticosa Pall. × P. pensylvanica L.) with the Maack bird cherry (Prunus padus L.) (Blažková, Hlušičková, 2002). PN was originated from 'Vladimirskaya' × 'Polevka' × Padus mackii (Rupr.)…”
Section: Methodsmentioning
confidence: 99%
“…Cerapadus was produced in Russia by I. V. Michurin in 1935 from a cross of cherry 'Ideal' (Prunus fruticosa Pall. × P. pensylvanica L.) with the Maack bird cherry (Prunus padus L.) (Blažková, Hlušičková, 2002). PN was originated from 'Vladimirskaya' × 'Polevka' × Padus mackii (Rupr.)…”
Section: Methodsmentioning
confidence: 99%
“…For example, all the cultivars on 'Gisela 5' were more damaged compared to the same cultivars on 'Gisela 6' . Differ-ences among the rootstocks in terms of cold resistance have been indicated by some studies (Durner 1990;Webster 1995;Callesen, Vittrup 1996;Szabo et al 1996;Webster, Schmidt 1996;Lang et al 1997;Prive, Embree 1997;Quamme, Brownlee 1997;Blažková, Hlušičková 2002). Callesen, Vittrup (1996) reported that a big difference in the frost damage to flowers was found among the rootstocks and 'Colt' showed the most severe damage.…”
Section: Methodsmentioning
confidence: 99%